The Role of the Optical Stretcher Is Crucial in the Investigation of Cell Mechanics Regulating Cell Adhesion and Motility - Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2019)
The mechanical properties of cells, tissues and the surrounding extracellular matrix environment play important roles in the process of cell adhesion and migration. In physiological and pathological processes of the cells, such as wound healing and cancer, the capacity to migrate through the extracellular matrix is crucial. Hence biophysical techniques were used to determine the mechanical properties of cells that facilitate the various migratory capacities. Since the field of mechanobiology is rapidly growing, the reliable and reproducible characterization of cell mechanics is required that facilitates the adhesion and migration of cells. One of these cell mechanical techniques is the optical stretching device, which was originally developed to investigate the mechanical properties of cells, such as the deformation of single cells in suspension. After discussing the strengths and weaknesses of the technology, the latest findings in optical stretching-based cell mechanics are presented in this review. Finally, the mechanical properties of cells are correlated with their migratory potential and it is pointed out how the inhibition of biomolecules that contribute to the to the maintenance of cytoskeletal structures in cells affect their mechanical deformability.